Ventilation of poultry houses - Sabiniak, Henryk (Instal, 2023)
The work includes requirements for rearing poultry to ensure its welfare. The final result is the design of the installation of mechanical exhaust ventilation in the part of the poultry production room and mechanical supply and exhaust ventilation in other rooms where people stay. The study specifies the size of the stocking density of birds in the hen house and the number of people production. On the basis of the calculations, elements of ventilation systems were selected based on catalogs: chimneys, exhaust and gable roof fans, air intakes. Calculations of air flow resistance in ducts were made, on the basis of which the remaining necessary part of the ventilation fittings was selected, such as: ducts, ventilation grilles, air handling units, intakes and launchers